Gallipoli - Moorehead, Alan, 1910-1983 (New York : Harper & Brothers Publishers, 1956)
When Turkey unexpectedly sided with Germany in World War I, Winston Churchill conceived a plan: smash through the Dardanelles, reopen the Straits to Russia, and immobilize the Turks. On the night of March 18, 1915, this plan nearly succeeded -- the Turks were virtually beaten. But poor communication left the Allies in the dark, allowing the Turks to prevail and the Allies to suffer a crushing quarter-million casualties. A chronicle of adventure, suspense, agony, and heroism, Gallipoli brings fully to life the tragic waste in human life, the physical horror, and the sheer heartbreaking folly of fighting for impossible objectives with inadequate means on unknown, unmapped terrain.
Includes bibliographical references (pages 371-372) and index.
Keywords: World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula; Military campaigns; Turkey -- Gallipoli Peninsula